1998
DOI: 10.3171/foc.1998.4.6.10
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychosocial need and needs resolution on quality of life in patients with brain tumors

Abstract: The diagnosis of cancer of the central nervous system (CNS) is often the diagnosis of an incurable, progressive disease with devastating effects on the physical, psychosocial, and cognitive functioning of patients. Because many of the treatment options are noncurative in nature, issues related to quality and quantity of life become paramount. The purpose of the authors' research was to explore the prevalence of psychosocial needs in this cancer population and to determine whether these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
1
10
0
2
Order By: Relevance
“…Unmet needs were found to have a significantly negative effect on QOL of breast cancer patients, which confirms a Japanese study27 and another study with brain tumor patients 28. Our findings suggest that interventions based on specific unmet needs could result in ameliorating depression of breast cancer survivors and enhancing their QOL.…”
Section: Discussionsupporting
confidence: 86%
“…Unmet needs were found to have a significantly negative effect on QOL of breast cancer patients, which confirms a Japanese study27 and another study with brain tumor patients 28. Our findings suggest that interventions based on specific unmet needs could result in ameliorating depression of breast cancer survivors and enhancing their QOL.…”
Section: Discussionsupporting
confidence: 86%
“…They have been utilized frequently in the area of cancer as a first step in designing needs‐tailored interventions 27–36. The importance of assessing needs is underscored by several findings: 1) unmet needs have been associated with poorer QOL37; 2) attention to psychosocial needs has been linked with higher patient satisfaction with medical care38; and 3) provision of “unwanted” interventions that do not fit with personal needs may actually have detrimental effects 39…”
mentioning
confidence: 99%
“…Previous studies suggested that there are moderate-to-strong associations between patients' perceived needs and psychological distress and/or quality of life (9), and that unmet needs are correlated with a low quality of life (10). Individual patients vary in their supportive care needs.…”
Section: Introductionmentioning
confidence: 99%